Margin calculation for multiple lung metastases treated with single-isocenter SBRT. (September 2021) - van Timmeren, Janita E.; Hoogeman, Mischa S.; Ehrbar, Stefanie; Mayinger, Michael; Andratschke, Nicolaus; Guckenberger, Matthias; Tanadini-Lang, Stephanie
Highlights: Safety margin calculation for single-isocenter SBRT of multiple lung metastases. Relative inter-lesion motion is compensated by an additional 1 mm margin. Pleural attachment is characterized with reduced inter-lesion position variation. For 65% dose prescriptions, random errors contribute to the margin only in SI. Abstract: Background and purpose: A single-isocenter stereotactic body radiotherapy (SBRT) approach for multiple lung metastases has the potential to lower cumulative patient dose and reduce overall treatment time. However, the magnitude of inter-lesion position variation is currently unknown and not incorporated in margin calculations. The aim of this study was to quantify inter-lesion position variation and calculate safety margins for single-isocenter lung SBRT. Materials and methods: A total of 83 pairs of pulmonary metastases from 42 NSCLC patients were used to calculate relative inter-lesion position variation by lesion-based registration of planning CT and verification CBCT. Furthermore, β-value assessment of van Herk's margin formula was performed by evaluating the distance between planned and blurred dose profiles of simulated spherical lesions, to evaluate its validity for heterogeneously planned dose distributions. Population-based ITV to PTV margins were calculated using the entire dataset and using subgroups with significant differences in relative inter-lesion position variation. Results: The mean ± SD inter-lesion position variation was 1.2 ± 1.1 mm as 3D-vector. Inter-lesion position variation was significantly increased if ≥1 lesion was not attached to the pleura or lesions were distant. The simulation showed that the combined SD of the random errors contributed to the margin only in the SI direction with 0.25 ∙ σ t o t for a 65% dose prescription. When incorporating inter-lesion position variation, the safety margins increased from 5.6, 5.8, 5.2 mm (AP, SI, LR) to 6.0, 6.6, 5.5 mm for the entire cohort. Conclusion: Relative inter-lesion position variation is influenced by inter-target distance and location and can be compensated with additional safety margins of <1 mm using single-isocenter SBRT.